Витоки, перебіг, наслідки Голодомору 1932–1933 років на Поділлі - Гальчак, С.; Федорук, О. (Краєзнавство, 2022)
У статті на основі архівних джерел, матеріалів преси та праць істориків розглядаються витоки, перебіг, наслідки Голодомору 1932–1933 років – жахливої трагедії, що мала місце на Поділлі. Опираючись на базові принципи історичного пізнання (історизму, науковості, об’єктивності, системності, всебічності, критичного підходу до аналізу джерельного матеріалу), використовуючи проблемно-хронологічний, структурно-системний, порівняльно-системний, порівняльно-історичний, статистично-аналітичний та інші загальнонаукові та спеціально-історичні методи, встановлено об’єктивну картину вчиненого більшовицькою владою злочину, в результаті якого лише на одній Вінниччині від голодної смерті загинуло подолян значно більше, ніж під час Другої світової війни. З’ясовано, що Голодомор мав конкретні соціально-економічні та національно-політичні передумови. Аналізуючи соціально-економічні витоки трагедії, звернено увагу на встановлення в країні жорсткої однопартійної системи, авторитаризму, розгортання владою свідомої боротьби проти власного селянства, нещадного його пограбування, перетворення на люмпенів, шляхом примусової колективізації, яку генсек Й. Сталін спершу розглядав як засіб накопичення коштів для здійснення індустріальних перетворень, безмірної викачки хліба, розправою над так званим «куркульством» – «останнім експлуататорським класом», подолання реального опору селян, для якого радянське керівництво повсюдно застосовувало терор і примус. Спричинивши великий голод в Україні, сталінський режим переслідував ще одну злочинну мету – викорінення національної автентичності, самобутності українців, що в результаті призвело до демографічної катастрофи, неприхованого етноциду – вбивства за етнічною ознакою. Наукова новизна статті визначається акцентуванням уваги на необхідності вивчення вчинення більшовицькою владою страшного злочину – зумисно організованого нею Голодомору 1932–1933 років, визнаного Верховною Радою України, багатьма парламентами світу геноцидом українського народу. Based on archival sources, press materials, and the works of historians, the article examines the origins, course, and consequences of the famine of1932\1933 which is a terrible tragedy that took place in the breadbasket of the world - Ukraine, in particular, in generous with abundant harvests Podillia region. Within the basic principles of historical knowledge (historicism, scientificity, objectivity, systema- ticity, comprehensiveness, critical approach to the analysis of source material), using problem-chronological, structural-systemic, comparative-systemic, comparative-historical, statistical-analytical and other general scientific and special-historical methods, an objective picture of the crime committed by the Bolshevik authorities was depicted. As a result of this crime there died of starvation more Podillia residents in Vinnytsia alone than during the Second World War. It was found that the crime had specific socio-economic and national-political prerequisites. Analyzing the socioeconomic origins of the tragedy, the authors’ attention is drawn to the establishment of a rigid one-party system in the country, authoritarianism, the deployment of a conscious struggle by the authorities against their own peasantry, their merciless robbery, transformation into lumpens, through forced collectivization, which Stalin initially considered as a means of accumulating funds for the implementation of industrial transformations, excessive pumping of bread, the crackdown on the so-called “kurkulstvo” - the “last exploitative class”, overcoming the real resistance of the peasants, for which the Soviet leadership used terror and coercion everywhere. Having caused a great famine in Ukraine, the Politburo of the Bolsheviks pursued another criminal goal - the eradication of national authenticity, the identity of Ukrainians, which ultimately led to a demographic catastrophe, undisguised ethnocide - murder on ethnic grounds. At the same time, nothing can justify the actions of the authorities, aimed at creating an artificial famine, which took away millions ofpeople, led to cases of cannibalism, and awakened animal instincts in people... The scientific novelty of the article is determined by focusing attention on the need to study the terrible crime committed by the Bolshevik government - the Holodomor of 1932-1933, which was delibe-rately organized by them, recognized by the Verkhovna Rada of Ukraine and many parliaments of the world as the genocide of the Ukrainian people.